The Psychological Gnosticism of Mystic Experience: A Critical Appraisal of Al-Qushayri, Al-Hujwiri, James and Iqbal (Al-Qamar, 2024)
Being a part of this spatio-temporal “phenomena” and desiring the knowledge of the “nuoma” or “Divine Reality” which is above from our commonly known capabilities and conventional manners of acquiring knowledge through a particular way of meditation and absorbing esoteric experience is the main feature of mysticism. Thus due to this manifold nature of mysticism, these questions appear: What is the nature of this experience? What are its basic characteristics? What would be the psychological states that a mystic would be subjsct to the experience? How this can be experienced? Is it either a result of personal endeavoures or is it  just a agranted blessing? Wheater it is religious or not?Is it to be arriticulated to other beings? And so on. They are the question which will be answered in this research.Thus, the present article presents the views of two ancient Mystics along-with the views of a psychologist and a philosopher. This will be revealed that how much importance occupied by mysticism in epistemology and how much vast and wide-ranging it is.